EFFECT OF COMMUNICATING TEST RECORD TO PARENTS ON STUDENTS’ PERFORMANCE - Khokhar, Abdul Rehman; Iqbal, Tehseen; Khan, Abdul Ghaffar; Rehman, Qurrat ul Ain (Pakistan Journal of Physiology, 2015)
Students’ academic performance is affected by multiple factors but a major factor is teacher parent communication regarding students’ progress in studies. Methods: The study objective was to assess the effect of intervention i.e. parental involvement, which might have improved the academic performance. This was a cross-sectional, interventional study. Simple random sampling technique was used. Students’ internal assessment test record (pre-intervention) was communicated to their parents. Any change in their academic performance was noted and marks obtained in internal assessment tests were compared with the marks obtained in send up examination (post-intervention). Data were analysed on SPSS-18; Mean±SD and p-values were calculated. Results: The pre-interventional marks obtained were 50.02±9.82 and post-interventional marks obtained were 52.47±8.99. The pre-interventional marks obtained by male students were 46.80±10.56 and post interventional marks obtained were 49.99±10.01. Female students pre-interventional marks obtained were 53.25±9.09 and post-interventional marks obtained were 58.94±7.97. Conclusion: The designed intervention resulted in significant improvement in academic performance. Among girl students’ improvement in academic performance was better than in boys. Parental involvement is significantly (p<0.05) and positively associated with academic performance.